Treatment of Experimentally Induced Cranial Cruciate Ligament Ruptures with Autografts in Goats: Physical, Radiographic, Arthroscopic and Histopathological Evaluations - Bayrak, Sema Çakır; Canpolat, İbrahim; Eröksüz, Hatice (My University, 2025)
Cranial cruciate ligament rupture, a significant cause of posterior extremity lameness, is an important concern in veterinary orthopedics. Three primary methods have been described for treating CCL ruptures: intra-articular, extra-articular, and osteotomy techniques. Both autogenous and synthetic materials are preferred for the intra-articular technique. For intra-articular stabilization, autografts such as skin, fascia lata, ligament, bone-patellar ligament, and tendons are used. In this study, two different autografts, the Musculus Peroneus Longus (MPL) and the Musculus Tibialis Cranialis (MTC) were employed using the intra-articular stabilization method to treat CCL ruptures. The study involved 12 female Anatolian Black Goats, averaging 38 kg in weight and aged between 3-4 years. The goats were randomly divided into two groups. MPL and MTC autografts were utilized for treating CCL ruptures through the intra-articular stabilization method. General anesthesia was induced with intramusculer injections of 11 mg/kg ketamine hydrochloride following 0.1 mg/kg xylazine hydrochloride as premedication. After inducing general anesthesia, the animals underwent surgery according to the intra-articular stabilization method. Physical, radiographic, and arthroscopic examinations were performed up to six months post-operation. At the six-month mark, all subjects were euthanized for macroscopic and microscopic examination of the knee joints. Intra-articular stabilization with MPL and MTC tendon autografts for treating CCL rupture was evaluated through physical, radiographic, arthroscopic, macroscopic, and histopathological assessments. The results indicated no complications during the six months following the CCL ruptures, confirming the autografts' effectiveness. Consequently, the findings suggest that the autografts utilized can effectively repair ruptured CCL and provide a viable treatment option.
Keywords: Goat; arthroscopy; cranial cruciate ligament; autograft; intraarticular stabilization